2016
DOI: 10.1177/0192623316660768
|View full text |Cite
|
Sign up to set email alerts
|

Findings in Historical Control Harlan RCCHan™

Abstract: Vehicle control Harlan RCCHan™:WIST rats were examined to provide control data for subsequent studies. The rats (180 male and 180 female) were dosed daily via oral gavage with reverse osmosis water for up to 104 weeks. At necropsy, body weights and macroscopic findings were recorded and tissues were collected for histopathology. The mean body weight at terminal sacrifice was 687 g for males and 466 g for females. The overall survival rate was 62% for males and 59% for females. The most common cause of death fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The cause of death was attributed to various tumors that were responsible for the cause of death in the studies evaluated; however, the most common tumor leading to death were pituitary neoplasms (44.7% in males and 58.1% in females) which is similar in many rat oncogenicity studies of different rat strains. 2,12 The other common neoplasms (>1%) were mammary neoplasm in females (24.6%), skin neoplasms (5.7% in males and 1.1% in females), hematolymphoid neoplasms (2.5% in males, 0.7% in females), and neoplasms in brain (1.5% in males and 0.5% in females). Mammary gland neoplasm, considered a major cause of unscheduled euthanasia and death, 13 was the second most common neoplasm recorded in females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of death was attributed to various tumors that were responsible for the cause of death in the studies evaluated; however, the most common tumor leading to death were pituitary neoplasms (44.7% in males and 58.1% in females) which is similar in many rat oncogenicity studies of different rat strains. 2,12 The other common neoplasms (>1%) were mammary neoplasm in females (24.6%), skin neoplasms (5.7% in males and 1.1% in females), hematolymphoid neoplasms (2.5% in males, 0.7% in females), and neoplasms in brain (1.5% in males and 0.5% in females). Mammary gland neoplasm, considered a major cause of unscheduled euthanasia and death, 13 was the second most common neoplasm recorded in females.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroadenoma and mammary carcinoma are the most common mammary neoplasms noted in other studies in rats of different strains. 6,2,12 Other mammary tumors of low incidence included adenolipoma, anaplastic carcinoma, carcinosarcoma, and fibroma (Table 10; Figures 18 and 19). Carcinosarcoma contains both epithelial and mesenchymal cell components which are malignant.…”
Section: Mammary Glandmentioning
confidence: 99%
“…Otherwise, degenerate and inflammatory aortic changes have not been reported in adults of strains of rats and mice commonly used in nonclinical safety studies. 13,14 We are not aware of reports of spontaneous aortic aneurysm in nonrodent species used in toxicity testing.…”
Section: Introductionmentioning
confidence: 99%
“…However, few reports have been published so far discussing a comprehensive analysis of spontaneous lesions in aged rats of this strain, especially non-neoplastic lesions. Only Blankenship et al reported microscopic findings of various lesions seen in routine toxicological studies 6 . The present study highlights our experience with naturally occurring neoplastic and non-neoplastic lesions in 39 male RccHan:WIST rats at 2 years of age.…”
mentioning
confidence: 99%